PENANGGULANGAN DAMPAK AKTIVITAS DEKAT TERHADAP KEJADIAN MIOPIA PADA ANAK-ANAK SEKOLAH DI MASA PANDEMI COVID-19 - Murni Marlina Simarmata; Ferry Doringin; Lorentius Wahana Dika (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
COVID-19 caused major disruptions in daily activities for children throughout the world as schools and extracurricular activities shut down. Some reports indicated an increace in myopia among children due to the increase near work and decrease of outdoor activity during the pandemic. This literature research was aimed at evaluating evidences of near work as contributing factor to myopia, and of outdoor activity as protective factor. Based on the evaluation, the researcher suggested serveral inmportant steps to reduce the negative impact of near work for school-children.